Split Variational Inclusion and Fixed Point Problem for Asymptotically Nonexpansive Semigroup in Hilbert Spaces: Issara Inchan - Team, Support (Thai Journal of Mathematics, 2020)
The main objective of this paper is to introduced the iterative method for the split variational inclusion and asymptotically nonexpansive semigroups in Hilbert space. We study the iterative scheme and prove the strong convergence to a common solution of the split variational inclusion and the set of common fixed points of one-parameter asymptotically nonexpansive semigroups. The results presented in this paper improved the result of Wen and Chen [D.J. Wen, Y.A. Chen, Iterative methods for split variational inclusion and fixed point problem of nonexpansive semigroup in Hilbert spaces, Journal of Inequalities and Applications (2015)], and many authors.